2020
DOI: 10.3389/fgene.2020.603144
|View full text |Cite
|
Sign up to set email alerts
|

MiR-144-3p Targets FoxO1 to Reduce Its Regulation of Adiponectin and Promote Adipogenesis

Abstract: MicroRNAs (miRNAs), as a series of important short-chain non-coding RNAs, play an important post-transcriptional role in many biological activities, including adipogenesis. miR-144 is significantly upregulated in type II diabetes (T2D), and is considered to be an important biomarker for T2D. However, although the occurrence of T2D is inextricably linked to adipogenesis, whether miR-144 directly regulates adipogenesis remains to be further explored. In this paper, we demonstrate that miR-144 has a higher expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Remarkably, Lin et al demonstrated that miR-144 targets Foxo1 , thus reducing its expression and inhibiting its promotional effect on adiponectin, thereby alleviating the inhibitory effect of adiponectin on adipogenesis in an experimental model ( 102 ). A study performed by Komaya et al reported that miR-33b showed high expression in the liver, and its expression was increased in response to cholesterol overload, using genetically modified mice, miR-33 knockout mice, and miR-33b Knock in mice; as a result, miR-33b showed increased atherogenic potential ( 103 ).…”
Section: Mirnas In Metabolic Alterationsmentioning
confidence: 99%
“…Remarkably, Lin et al demonstrated that miR-144 targets Foxo1 , thus reducing its expression and inhibiting its promotional effect on adiponectin, thereby alleviating the inhibitory effect of adiponectin on adipogenesis in an experimental model ( 102 ). A study performed by Komaya et al reported that miR-33b showed high expression in the liver, and its expression was increased in response to cholesterol overload, using genetically modified mice, miR-33 knockout mice, and miR-33b Knock in mice; as a result, miR-33b showed increased atherogenic potential ( 103 ).…”
Section: Mirnas In Metabolic Alterationsmentioning
confidence: 99%
“…Some miRNAs detected in skeletal muscle correspond to two key pathways: one related to mitochondria and energy metabolism and the other related to skeletal muscle growth. Several miRNAs, including miR-338, miR-335, and miR-144, are related to mitochondria and energy metabolism [ 20 , 21 ]. More than 90% of cellular energy is produced by mitochondria through oxidative phosphorylation (OXPHOS) [ 55 ].…”
Section: The Mirnas Functions In Feed Efficiencymentioning
confidence: 99%
“…This takes place in the case of miR-144 and FOXO1. miR-144 targets FoxO1 mRNA, thus reducing its expression and inhibiting its promotional effect on adiponectin, thereby alleviating the inhibitory effect of adiponectin on adipogenesis in porcine preadipocytes [ 120 ]. In human obesity, serum miR-144 is a marker of insulin resistance, and its levels are elevated in SAT and decrease after weight loss intervention [ 9 , 82 , 121 ].…”
Section: Microrna In the Regulation Of Adipose Tissue Functionmentioning
confidence: 99%